Right ventricular global dysfunction score: a new concept of right ventricular function assessment in patients with heart failure with reduced ejection fraction (HFrEF) - Benes, Jan; Kotrc, Martin; Wohlfahrt, Peter; Kroupova, Katerina; Tupy, Marek; Kautzner, Josef; Melenovsky, Vojtech (Frontiers in Cardiovascular Medicine, 2023)
Background Right ventricular (RV) function is currently being evaluated solely according to the properties of RV myocardium. We have tested a concept that in patients with heart failure with reduced ejection fraction (HFrEF), RV assessment should integrate the information about both RV function as well as size. Methods A total of 836 stable patients with HFrEF (LVEF 23.6 ± 5.8%, 82.8% males, 68% NYHA III/IV) underwent echocardiographic evaluation and were prospectively followed for a median of 3.07 (IQRs 1.11; 4.89) years for the occurrence of death, urgent heart transplantation or implantation of mechanical circulatory support. Results RV size (measured as RV-basal diameter, RVD1) was significantly associated with an adverse outcome independent of RV dysfunction grade (p = 0.0002). The prognostic power of RVD1 was further improved by indexing to body surface area (RVD1i, p < 0.05 compared to non-indexed value). A novel parameter named RV global dysfunction score (RVGDs) was calculated as a product of RVD1i and the degree of RV dysfunction (1–4 for preserved RV function, mild, moderate and severe dysfunction, respectively). RVGDs showed a superior prognostic role compared to RV dysfunction grade alone (ΔAUC >0.03, p < 0.0001). In every subgroup of RVGDs (<20, 20–40, 40–60, >60), patients with milder degree of RV dysfunction but more dilated RV had similar outcome as those with more severe degree of RV dysfunction but smaller RV size (all p > 0.50), independent of tricuspid regurgitation severity and degree of pulmonary hypertension. Conclusion RV dilatation is a manifestation of RV dysfunction. The evaluation of RV performance should integrate the information about both RV size and function.